2012
DOI: 10.1371/journal.pone.0042344
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Peptide Binds to Cytochrome C Oxidase Subunit 1

Abstract: Extracellular and intraneuronal accumulation of amyloid-beta aggregates has been demonstrated to be involved in the pathogenesis of Alzheimer's disease (AD). However, the precise mechanism of amyloid-beta neurotoxicity is not completely understood. Previous studies suggest that binding of amyloid-beta to a number of macromolecules has deleterious effects on cellular functions. Mitochondria were found to be the target for amyloid-beta, and mitochondrial dysfunction is well documented in AD. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 60 publications
1
53
1
Order By: Relevance
“…These metabolic alterations in early stages of the disease and in patients diagnosed with AD correspond to ETC damage, particularly in the activity of the cytochrome C oxidase enzyme (Hernández-Zimbrón et al, 2012;Bobba et al, 2013). Experiments in transgenic mice have demonstrated the presence of this peptide within cellular organelles, which correlate with the magnitude of mitochondrial dysfunction caused by the inhibition of the ETC and with the degree of cognitive damage observed in this model of AD (Ghosh et al, 2013).…”
Section: Importance Of the Presence Of βA Peptide In Mitochondria Andmentioning
confidence: 73%
“…These metabolic alterations in early stages of the disease and in patients diagnosed with AD correspond to ETC damage, particularly in the activity of the cytochrome C oxidase enzyme (Hernández-Zimbrón et al, 2012;Bobba et al, 2013). Experiments in transgenic mice have demonstrated the presence of this peptide within cellular organelles, which correlate with the magnitude of mitochondrial dysfunction caused by the inhibition of the ETC and with the degree of cognitive damage observed in this model of AD (Ghosh et al, 2013).…”
Section: Importance Of the Presence Of βA Peptide In Mitochondria Andmentioning
confidence: 73%
“…This is particularly true for Alzheimer's disease which is characterized by the presence of extracellular senile plaques, mainly composed of amyloid‐β (Aβ) peptide and intracellular neurofibrillary tangles made up of hyperphosphorylated tau protein (Selkoe, 2004). Several studies demonstrate that the Aβ peptide accumulates progressively into mitochondria (Hansson Petersen et al., 2008; Manczak et al., 2006) where it inhibits the activities of the respiratory chain complex and thus oxidative phosphorylation ( Hernandez‐Zimbron et al., 2012; Lahmy, Long, Morin, Villard, & Maurice, 2015; Tillement, Lecanu, & Papadopoulos, 2011; Tsukada et al., 2014). The Aβ peptide can also potentially cause mPTP opening in vivo as it induces mitochondrial swelling, decreases mitochondrial membrane potential, and potentiates the effect of mPTP inducers in isolated brain mitochondria (Du et al., 2008; Moreira, Santos, Moreno, & Oliveira, 2001; Shevtzova, Kireeva, & Bachurin, 2001).…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%
“…60 Recent studies have shown that the Aβ can interact with cytochromes. 61 Addition of a stoichiometric amount of oxidized Cyt c (Soret at 410 nm) to reduced heme−Aβ (Soret at 383 nm) results in the appearance of a Soret band at 416 nm corresponding to reduced cytochrome c, with a shoulder at 364 nm corresponding to oxidized heme−Aβ. The formation of sharp Q bands at 520 and 550 nm characteristic of reduced …”
Section: Electron Transfermentioning
confidence: 99%